Relationships and traders in Madagascar - Fafchamps, Marcel; Minten, Bart (International Food Policy Research Institute, 1998)
This paper documents the role that personal relationships play in economic exchange. Original survey data show that agricultural traders in Madagascar perceive relationships as the most important factor for success in their business.Evidence details the extent to which relationships are used to serve a variety of purposes such as: the circulation of information about prices and market conditions; the provision of trade credit; the prevention and handling of contractual difficulties; the regularity of trade flows; and the mitigation of risk. Of these, the regularity of supply and demand and the sharing of risk appear particularly important. Larger and more pros-perous traders are those with quantitatively and qualitatively better relationships. Family plays little role in business beyond assistance at start-up.